Editorial - Pacheco Romero, José (2015)
Nutrition in women is an important issue today. Its importance will be valid throughout his life, from childhood to old age. In fact, from conception to death. If not, remember that good nutrition is essential when developing the new being, during the several weeks that grows in the womb -day to -day something faster than a building-, so, too, when the baby is born and from the first weeks of life, to cope with totally different than it did in the womb environment; when it develops and grows during childhood, -stage crucially, whose nutritional care depends subsequent physical, hormonal, intellectual development; when at puberty and adolescence activity unlike their endocrine, immune and reproductive systems, among others; when fully developed its role as a woman, you play, epic, breastfeeds; later, when their ovaries something weary begin their functional decline and body tissues change their turgor, firmness and elasticity; when at maturity, his vision, his heart and arteries, bones and joints, their defenses in involution, require many nutrients, not yet fully determined.